THE NEED TO INCREASE HUMAN DIGITAL COMPETENCE IN THE DIGITAL ECONOMY - Nabiyeva Nilufar Muratovna (European Science Publishing, 2024)
The rapid evolution of the digital economy has fundamentally transformed the landscape of human resources. As businesses navigate an increasingly interconnected and technology-driven world, the role of HR has expanded beyond traditional functions to encompass strategic initiatives that drive innovation and competitiveness. In this new era, human resources professionals must adapt to emerging trends, leveraging digital tools and data analytics to recruit, develop, and retain talent effectively. This article explores the pivotal changes and challenges in human resources within the digital economy, highlighting the strategies and skills necessary for success in a dynamic, ever-changing environment.
Keywords: Human resources, digital competency, remote work, data-driven HR, Gig economy, DEI- diversity, equity and inclusion.